In the Cobweb of Horror: Poe’s and Lovecraft’s Characters Bound with the Fibers of Dread (American & British Studies Annual, 2013)
This paper focuses on the analysis of the concept of fear in the works of Edgar Allan Poe and Howard Phillips Lovecraft. Certain crucial, interconnected issues are dealt with which show the similarities and differences between the two authors‘ works: sources of fright, lunacy and the role of setting. This essay engages only with the horror stories written by Poe and Lovecraft, not with their short stories associated with other genres (satire, fantasy, etc.).
Keywords: Poe; Lovecraft; horror; sci-fi; gothic; fear; lunacy; setting